Pengaruh Fitur Flash Sale dan Gratis Ongkos Kirim Pada Platform Shopee terhadap Keputusan Pembelian Konsumen di Jakarta Timur - Maulidya Edelweis; Purwatiningsih Purwatiningsih; Ratih Setyo Rini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyse the influence of flash sales and free shipping on consumer purchasing decisions for Shopee products. The research was conducted from October to December with a quantitative approach, involving 100 respondents as a sample. Data analysis includes data quality tests, classical assumption tests, hypothesis tests, multiple regression analysis, and determination coefficient tests with IBM SPSS 25 software. The results of the partial test showed that flash sale (X1) had no significant effect on consumer purchase decisions (Y) with a T value of -0.996 < 1.661 and a significance of 0.322 > 0.05. On the contrary, free shipping (X2) had a significant effect on consumer purchase decisions (Y) with a T value of 5.982 > 1.661 and a significance of 0.000 < 0.05. The F test shows that simultaneously flash sale (X1) and free shipping (X2) have a significant influence on consumer purchase decisions (Y) with an F value of 17.947 > F table 3.090 and a significance of 0.000 < 0.05. These results indicate that the two variables together have a positive influence on consumer purchase decisions on Shopee products.